Anthropometric and physiological profile of young male athletes of Olympic triathlon - Gianfelici, A.; Tamburri, R.; Miglio, M.; Bottoni, A.; Bomprezzi, A.; Faina, M. (Medicina dello Sport, 2012)
Aim. The Triathlon is an endurance sport event consisting of swimming, biking and running; these events are placed back-to-back in immediate sequence and a competitor`s official time includes the time required to "transition". The purpose of the present study was to determine the anthropometric and physiological profile of young triathletes (OTA) (19-23 years) compared to a group of elite OTA, and to evaluate the profiles` differences in order to establish if the younger group already has such qualities to succeed. Methods. Seven male OTA, selected among the best Italian ranking between the age of 19 and 23, volunteered to participate into the study. Anthropometric measurements included body weight, height, and bioelectrical impedance measurements; physiological measurements included aerobic and anaerobic test. Results. The results showed (age 21.7±1.28 years; height 177.9±5.76 cm; body mass (BM) 69.6±3.1 kg; body fat mass 6±1.97%; fat free mass 65.3±1.99 kg) the VO2peak was 71.4±3.96 mlO2*kg-1*min-1, 70.3±6.65 mlO2*kg-1*min-1 and 67.6±10.83 mlO2*kg-1*min-1, respectively on cyclergometer, on treadmill and on swimming flume. The peak power (PP) on Win30 test was 804.4±83.88 W (11.5±1.36 W/kg BM). Conclusion. This study shows that the young triathletes had similar body structures, similar aerobic data and similar anaerobic values compared with the elite Italian OTA and elite Portuguese triathletes.